Determinan Intention To Stay yang Dimediasi Organizational Commitment Pada Karyawan E-Commerce di DKI Jakarta - Ahmad Hilalluddin; Justine Tanuwijaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The high turnover rate in the e-commerce industry requires companies to have effective strategies for employee retention. This study aims to analyze the influence of talent management practices, workplace flexibility, and ethical leadership on employee intention to stay, with organizational commitment as a mediating variable. The study used a quantitative approach through a survey method of 230 e-commerce employees domiciled in DKI Jakarta. Data analysis was conducted using Structural Equation Modeling (SEM) with the help of AMOS software. The results showed that talent management practices did not have a positive effect on intention to stay, but did have a positive effect on organizational commitment. Workplace flexibility did not have a positive effect on either intention to stay or organizational commitment. Conversely, ethical leadership had a positive effect on intention to stay and organizational commitment. In addition, organizational commitment was proven to have a positive effect on intention to stay. The results of the mediation test showed that organizational commitment was able to mediate the influence of talent management practices and ethical leadership on intention to stay, but did not mediate the effect of workplace flexibility. This study concluded that strengthening talent management and ethical leadership are key factors in increasing employee commitment and sustainability in the e-commerce industry.